TINJAUAN MAFSADAH MASLAHAH TERHADAP PERNIKAHAN USIA DINI KARENA PAKSAAN ORANG TUA DI KECAMATAN PEUSANGAN KABUPATEN BIREUEN - Azhari (Jurnal Syariah dan Ekonomi Islam, 2025)
Islam as a guideline for human life to achieve true happiness, both worldly andhereafter happiness. In the Qur'an it is stated that, marriage is happiness (sakinah).From marriage it is expected to get offspring, tranquility and peace. Early marriagethat has occurred lately because it usually leads to disobedience and adulterywhose victims are mostly young people. Pros and cons have emerged against earlymarriage, some support it and some reject it. This study aims: 1) to find out theimplementation of early marriage in Peusangan District, Bireuen Regency, (2) tofind out the Islamic legal review of early marriage in Peusangan District, BireuenRegency. This study is a field study using a qualitative approach, implemented inPeusangan District, Bireuen Regency. Data collection techniques throughinterviews, observation and documentation. Data analysis techniques are carriedout through data reduction, data presentation and data verification. The results ofthe study indicate that early marriage in Peusangan District is due to economicfactors, dating factors, mutual liking factors, and family customs factors that havebecome habits. However, households that marry at an early age are lessharmonious and happy, because there are often household disputes and quarrels.A review of Islamic law on early marriage in Peusangan District, Regency,according to Islamic law, the opinion of religious leaders is valid, the mostimportant thing is that the marriage meets the requirements and pillars of marriage.However, on the other hand, we must also look at the benefit side.